Development Of Augmented Reality Using The Four-D Model In Ipas Learning For Grade 5 Elementary School - Robi’ati Fauziyah; Achmad Noor Fatirul; Hartono (At Turots: Jurnal Pendidikan Islam, 2026)
This research aims to develop Augmented Reality (AR) learning media for the IPAS subject on the topic of Harmony in Ecosystems for 5th-grade students at SD Negeri 1 Kedungpring, Lamongan Regency. The research is motivated by low student learning outcomes, with 57% of students not meeting the Minimum Completeness Criteria (KKM), and learning activities that are monotonous with minimal use of interactive digital media. This development research employed the Four-D (4D) model (Define, Design, Develop, Disseminate). The resulting final product is an AR-based teaching module that is interactive, easily accessible, and engaging. The validation results from material experts, design experts, and media experts showed a very good category with an overall average validation score of 4.68 and a validity percentage of 94%. Product trials also indicated a positive response from peers and students. In conclusion, the developed Augmented Reality media is declared feasible/valid and effective in enhancing student motivation and understanding of the IPAS material , while also facilitating teachers in visualizing abstract concepts through interactive three-dimensional objects.